Analisis Employee Engagement, Teamwork, Career Development, Work Life Balance Terhadap Kinerja Pegawai pada PT. Lintong Bintang Makmur Medan - Robinhot Gultom; Jeudi A. T. P. Sianturi (Universitas Methodist Indonesia, 2025)
This study aims to determine the effect of employee engagement, teamwork, career development, and work-life balance on employee performance at PT. Lintong Bintang Makmur Medan. This research uses a quantitative approach, with a sample size of 81 respondents. Based on the t-test results, it can be concluded that Employee Engagement partially has no effect on employee performance. Teamwork, Career Development, and Work-Life Balance partially have a significant effect on employee performance. Based on the F-test, it can be concluded that Employee Engagement, Teamwork, Career Development, and Work-Life Balance significantly influence employee performance. The coefficient of determination (Adjusted R-Square) analysis yielded a coefficient of determination of 0.677, indicating that 67.7% of employee performance can be explained by Employee Engagement, Teamwork, Career Development, and Work-Life Balance. The remaining 32.3% is explained by other variables or factors not examined in this study.